Live cell imaging of germination and outgrowth of individual bacillus subtilis spores; the effect of heat stress quantitatively analyzed with SporeTracker. - Rachna Pandey (PLoS ONE, 2013)
Spore-forming bacteria are a special problem for the food industry as some of them are able to survive preservation processes. Bacillus spp. spores can remain in a dormant, stress resistant state for a long period of time. Vegetative cells are formed by germination of spores followed by a more extended outgrowth phase. Spore germination and outgrowth progression are often very heterogeneous and therefore, predictions of microbial stability of food products are exceedingly difficult. Mechanistic details of the cause of this heterogeneity are necessary. In order to examine spore heterogeneity we made a novel closed air-containing chamber for live imaging. This chamber was used to analyze Bacillus subtilis spore germination, outgrowth, as well as subsequent vegetative growth. Typically, we examined around 90 starting spores/cells for ≥4 hours per experiment. Image analysis with the purposely built program "SporeTracker" allows for automated data processing from germination to outgrowth and vegetative doubling. In order to check the efficiency of the chamber, growth and division of B. subtilis vegetative cells were monitored. The observed generation times of vegetative cells were comparable to those obtained in well-aerated shake flask cultures. The influence of a heat stress of 85°C for 10 min on germination, outgrowth, and subsequent vegetative growth was investigated in detail. Compared to control samples fewer spores germinated (41.1% less) and fewer grew out (48.4% less) after the treatment. The heat treatment had a significant influence on the average time to the start of germination (increased) and the distribution and average of the duration of germination itself (increased). However, the distribution and the mean outgrowth time and the generation time of vegetative cells, emerging from untreated and thermally injured spores, were similar.